2013
DOI: 10.1155/2013/671204
|View full text |Cite
|
Sign up to set email alerts
|

Revision: Variance Inflation in Regression

Abstract: Variance Inflation Factors (VIFs) are reexamined as conditioning diagnostics for models with intercept, with and without centering regressors to their means as oft debated. Conventional VIFs, both centered and uncentered, are flawed. To rectify matters, two types of orthogonality are noted: vector-space orthogonality and uncorrelated centered regressors. The key to our approach lies in feasible Reference models encoding orthogonalities of these types. For models with intercept it is found that (i) uncentered V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…The distinction between essential and nonessential multicollinearity and its diagnosis has not been not been adequately treated in either the scientific literature or in statistical software and this lack of information has led to mistakes in some relevant papers, for example Velilla [3] or Jensen and Ramirez [13]. This paper analyzes the detection of essential and nonessential multicollinearity from auxiliary centered and noncentered regressions, obtaining two complementary measures between them that are able to detect both kinds of multicollinearity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The distinction between essential and nonessential multicollinearity and its diagnosis has not been not been adequately treated in either the scientific literature or in statistical software and this lack of information has led to mistakes in some relevant papers, for example Velilla [3] or Jensen and Ramirez [13]. This paper analyzes the detection of essential and nonessential multicollinearity from auxiliary centered and noncentered regressions, obtaining two complementary measures between them that are able to detect both kinds of multicollinearity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the algebraic contextualization provided by Salmerón Gómez et al [12] will be complemented from an econometric point of view. This question was also presented by Jensen and Ramirez [13], striving to commit to a clarification of the misuse given to the VIF over decades since its first use, who insinuated: To choose a model, with or without intercept, is substantive, is specific to each experimental paradigm and is beyond the scope of the present study. It was also stated that: This differs between centered and uncentered diagnostics.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Dias & Castro () showed that the real impact on variance can be overestimated by the traditional VIF when the explanatory variables contain no redundant information about the dependent variable and stated that a corrected version of this multicollinearity indicator becomes necessary. In their diagnostic of collinearity, Jensen & Ramirez () made a distinction between centred and uncentred VIFs. Moreover, they pointed out the special relevance of uncentred VIF when the independent term plays an important role in the interpretation of the model.…”
Section: Introductionmentioning
confidence: 99%